2019
DOI: 10.1002/jcp.28058
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA replacement therapy in cancer

Abstract: Despite the recent progress in cancer management approaches, the mortality rate of cancer is still growing and there are lots of challenges in the clinics in terms of novel therapeutics. MicroRNAs (miRNA) are regulatory small noncoding RNAs and are already confirmed to have a great role in regulating gene expression level by targeting multiple molecules that affect cell physiology and disease development. Recently, miRNAs have been introduced as promising therapeutic targets for cancer treatment. Regulatory po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
156
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 211 publications
(161 citation statements)
references
References 228 publications
(287 reference statements)
0
156
0
5
Order By: Relevance
“…In pathological conditions, MiRNAs can negatively regulate gene expression and they are associated with tumor growth, apoptosis, invasion, and metastasis. In the past, several studies have indicated the ability of miRNAs in the inhibition of tumors as a critical option for the improvement of cancer therapy [4,5]. Tumor activator miRNAs, called oncomiRs, are overexpressed in various cancers.…”
mentioning
confidence: 99%
“…In pathological conditions, MiRNAs can negatively regulate gene expression and they are associated with tumor growth, apoptosis, invasion, and metastasis. In the past, several studies have indicated the ability of miRNAs in the inhibition of tumors as a critical option for the improvement of cancer therapy [4,5]. Tumor activator miRNAs, called oncomiRs, are overexpressed in various cancers.…”
mentioning
confidence: 99%
“…Interestingly, it could also be possible to restore the expression of a tumor suppressor miRNA by inserting genes coding for miRNAs into viral constructs, such as adenovirus-associated vectors. The aim of anti-miRs approaches is to silence oncogenic miRNAs using anti-miR oligonucleotides, miRNA sponges, miRNA masking, and small RNA inhibitors [102,103]. Anti-miR oligonucleotides are chemically modified antisense oligonucleotides.…”
Section: Mirnas As Therapeutic Targetsmentioning
confidence: 99%
“…Moreover, the functions of miRNAs are involved in the occurrence, development and metastasis of tumors. 7 For instance, Mirzaei et al reported that miR-29b has signi cant tumor-suppressive effects on chronic lymphocytic leukemia (CLL). 8 In addition, Zhou Y et al discovered that miR-130a acts as an oncogenic miRNA in gastric cancer.…”
Section: Introductionmentioning
confidence: 99%